Platelet-Mediated Protection of Cancer Cells From Immune Surveillance – Possible Implications for Cancer Immunotherapy - Schmied, Laurent; Höglund, Petter; Meinke, Stephan (Frontiers in Immunology, 2021)
The growing insights in the complex interactions between metastatic cancer-cells and platelets have revealed that platelet tumor cell interactions in the blood stream are an important factor supporting tumor metastasis. An increased coagulability of platelets facilitates the vascular evasion and establishment of solid tumor metastasis. Furthermore, platelets can support an immunosuppressive tumor microenvironment or shield tumor cells directly from engagement of cytotoxic lymphocytes as e.g. natural killer (NK) cells. Platelets are both in the tumor microenvironment and systemically the quantitatively most important source of TGF-β, which is a key cytokine for immunosuppression in the tumor microenvironment. If similar platelet-tumor interactions are of physiological relevance in hematological malignancies remains less well studied. This might be important, as T- and NK cell mediated graft versus leukemia effects (GvL) are well documented and malignant hematological cells have a high exposure to platelets compared to solid tumors. As NK cell-based immunotherapies gain increasing attention as a therapeutic option for patients suffering from hematological and other malignancies, we review the known interactions between platelets and NK cells in the solid tumor setting and discuss how these could also apply to hematological cancers. We furthermore explore the possible implications for NK cell therapy in patients with solid tumors and patients who depend on frequent platelet transfusions. As platelets have a protective and supportive effect on cancer cells, the impact of platelet transfusion on immunotherapy and the combination of immunotherapy with platelet inhibitors needs to be evaluated.